'Can you hear me now?' Phreaking the party line from operators to occupy. Issue 5 (3rd May 2016) - Donovan, Joan
ABSTRACT: Contemporary networked social movements are characterized by their innovative use of mobile phones, the Internet, and social media to coordinate collective action. From 2011 to 2012, I conducted an ethnographic study of a group of Occupy protesters called InterOccupy, who scheduled and moderated 2000 movement-wide conference calls. Drawing on the history of telephones, I clarify why the Occupy movement utilized conference calls to organize mobilizations during an intense period of police repression. I locate InterOccupy within the history of conference calls to draw out the affordances of conference systems as tools for convening distributed groups in real time. Tethering InterOccupy to the history of telephone operators from the 1920s to 1960s, who used switchboards to manage shared party lines, with the phone phreaks of the 1960s–1980s, hackers who explored the telephone network, illustrates how each group used similar tools, techniques, and protocols to form communities across vast distances. Using a webinar system to link up to 500 callers, InterOccupy were guided by the ethics of phone phreaks to open lines of communication coupled with the methods of telephone operators to bring voices together. Charting the history of voice-to-voice communication explains why InterOccupy picked up the phone to bring about social change at a time when other information and communication technologies were available.